Hazardous waste dewatering and dry mass reduction through hydrophobic modification by a facile one-pot, alkali-assisted hydrothermal reaction. (15th May 2019) - Li, Xiang; Wang, Jing; You, Jiguang; Yu, Pingfeng; Li, Xianying; Xue, Gang; Chen, Hong; Xu, Xianbao; van Agtmaal, Sjack; Alvarez, Pedro J.J.
Abstract: Hazardous waste dewatering is important for volume reduction and further treatment. Hazardous organic wastes with low ratio of free to bound water, and low flash point are difficult to dewater and pose an explosion risk for conventional thermal drying. Here, we develop a facile one-pot, alkali-assisted hydrothermal treatment (AHT) method for cost-efficient hazardous waste dewatering, dry mass minimization and volume reduction. Wet paint sludge (WPS), a hazardous organic waste, was reduced (79% by total weight and 52% by dry mass) by dewatering through AHT hydrophobic modification, and the product was nonflammable. Conversion of bound water to free water enhanced WPS dissolution for further decomposition. Alkali was critical for boosting ether demethylation in the solid phase, and cleavage of ethers forming alcohols that facilitated transfer of solid mass into the liquid phase. Polar functional groups were eliminated through AHT, which increased the relative abundance of hydrophobic functional groups on the surface of solid residues and promoted dewatering. We also demonstrate that AHT can be widely adapted and scaled up to treat various hazardous organic waste streams, which is of significant industrial and environmental interest. Graphical abstract: Image 1 Highlights: Alkali-assisted hydrothermal treatment (AHT) promoted hazardous waste dewatering. Wet paint sludge was reduced 79.1% by total weight and 52.1% by dry mass through AHT. Alkali was critical for boosting ether demethylation in the solid phase. Polar functional groups were eliminated and hydrophobic functional groups increased. AHT can be widely adapted and was scaled up to treat various organic hazardous waste.